Risk assessment, resistance monitoring and mechanism of field-evolved resistance to broflanilide in the tobacco cutworm, Spodoptera litura - Xiao Guo; Yilu Tong; Ren Li; Shengran Zhang; Daofeng Zhang; Cheng Qu; Xiaoli Ma; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Metagenomic analysis reveals differences in antibiotic resistance and transmission risks across various poultry farming models - Yanru Huang; Shuaizhou Zong; Dingting Xu; Jiwei He; Yaru Zhang; Min Qian; Yuxing Li; Bohai Guo; Jianzhong Han; Daofeng Qu (Science of The Total Environment, 2025)

Risk assessment, cross-resistance, biochemical mechanism and fitness cost of tetraniliprole resistance in the tomato pinworm Tuta absoluta - Cheng Qu; Jiaqi Yao; Qianyuan Zhan; Daofeng Zhang; Yunyi Li; Jianlei Huang; Ran Wang (Crop Protection, 2024)

Identification of microbial communities and multi-species biofilms contamination in seafood processing environments with different hygiene conditions - Jun Zhang; Zhong Lu; Lifang Feng; Daofeng Qu; Junli Zhu (Food Microbiology, 2024)

Baseline of susceptibility, risk assessment, biochemical mechanism, and fitness cost of resistance to dimpropyridaz, a novel pyridazine pyrazolecarboxamide insecticide, in Bemisia tabaci from China - Juan Tang; Cheng Qu; Qianyuan Zhan; Daofeng Zhang; Jinda Wang; Chen Luo; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Fabrication and characterization of sodium alginate/blueberry anthocyanins/hinokitiol loaded ZIF-8 nanoparticles composite films with antibacterial activity for monitoring pork freshness - Bohai Guo; Yun Sun; Qiuyue Guan; Zheng Luo; Lian Zhou; Zhenlan Xu; Jianzhong Han; Daofeng Qu (Food Chemistry, 2024)

Characterization and fitness cost analysis of two plasmids carrying different subtypes of bla in aquaculture farming - Yaru Zhang; Dingting Xu; Ze He; Jianzhong Han; Daofeng Qu (Food Microbiology, 2023)

CRISPR-Cas systems are present predominantly on chromosome and its relationship with MEGs in Vibrio species - Enbao Zhang; Wei Zhou; Jinzhi Zhou; Ze He; Yuqiao Zhou; Jianzhong Han; Daofeng Qu (Archives of Microbiology, 2022)

Fitness cost and compensation mechanism of sulfonamide resistance genes ( sul1 , sul2 , and sul3 ) in Escherichia coli - Yuqiao Zhou; Jiehong Fang; Zaeim Davood; Jianzhong Han; Daofeng Qu (Environmental Microbiology, 2021)
Summary The fitness cost of antibiotic resistance is a crucial factor to determine the evolutionary and transmission success of resistant bacteria. Exploring the fitness cost and compensation mechanism of antibiotic resistance genes (ARGs) in bacteria may effectively reduce the transmission of drug‐resistant genes in the environment. Engineered bacteria with the same genetic background that carry sulfonamide resistance gene were generated to explore the fitness cost of sulfonamide resistance gene in Escherichia coli . There were significant differences in the protein expression of the two‐component system pathway ( fliZ , fliA , fliC and lrhA ), folate biosynthesis pathway ( sul1 , sul2 and sul3 ), ABC transporter system ( ugpC , rbsA and gsiA ), and outer membrane pore protein OmpD through the comparative analysis of differential proteins compared to sensitive bacteria. Thus, we could speculate the possible fitness compensation mechanism. Finally, quantitative Real‐time PCR (qRT‐PCR) was used to verify the functions of some differential proteins at the transcriptional level. The fitness cost and compensatory evolution of antibiotic resistance are an essential part of bacterial evolution.